THE ROLE OF SPIRITUAL GUIDES FROM A PSYCHOLOGIST’S POINT OF VIEW - Kalam, Thomas (Journal of Dharma, 1980)
In times past when psychology used to be understood as the science of the soul, it might have been easier to speak of matters pertaining to spirituality from a psychologist’s point of view. We have come a long way from that time when the main concern of psychology was theoretical speculation regarding the invisible soul and its rational, immortal or spiritual nature. Instead of the soul, mind and behaviour have become the subject-matter of its study; instead of theoretical speculation, empirical research has become its methodology.